The Clinical Presentation of Culture-positive and Culture-negative, Quantitative Polymerase Chain Reaction (qPCR)-Attributable Shigellosis in the Global Enteric Multicenter Study and Derivation of a Shigella Severity Score: Implications for Pediatric Shigella Vaccine Trials. (12th October 2020) - Pavlinac, Patricia B; Platts-Mills, James A; Tickell, Kirkby D; Liu, Jie; Juma, Jane; Kabir, Furqan; Nkeze, Joseph; Okoi, Catherine; Operario, Darwin J; Uddin, Jashim; Ahmed, Shahnawaz; Alonso, Pedro L; et al.
Abstract: Background: Shigella is a leading cause of childhood diarrhea and target for vaccine development. Microbiologic and clinical case definitions are needed for pediatric field vaccine efficacy trials. Methods: We compared characteristics of moderate to severe diarrhea (MSD) cases in the Global Enteric Multicenter Study (GEMS) between children with culture positive Shigella to those with culture-negative, quantitative polymerase chain reaction (qPCR)-attributable Shigella (defined by an ipaH gene cycle threshold <27.9). Among Shigella MSD cases, we determined risk factors for death and derived a clinical severity score. Results: Compared to culture-positive Shigella MSD cases (n = 745), culture-negative/qPCR-attributable Shigella cases (n = 852) were more likely to be under 12 months, stunted, have a longer duration of diarrhea, and less likely to have high stool frequency or a fever. There was no difference in dehydration, hospitalization, or severe classification from a modified Vesikari score. Twenty-two (1.8%) Shigella MSD cases died within the 14-days after presentation to health facilities, and 59.1% of these deaths were in culture-negative cases. Age <12 months, diarrhea duration prior to presentation, vomiting, stunting, wasting, and hospitalization were associated with mortality. A model-derived score assigned points for dehydration, hospital admission, and longer diarrhea duration but was not significantly better at predicting 14-day mortality than a modified Vesikari score. Conclusions: A composite severity score consistent with severe disease or dysentery may be a pragmatic clinical endpoint for severe shigellosis in vaccine trials. Reliance on culture for microbiologic confirmation may miss a substantial number of Shigella cases but is currently required to measure serotype specific immunity. Abstract : Molecular methods identified Shigella more commonly than microbiologic culture in younger and stunted children. A simplified clinical score containing dehydration, hospitalization, and diarrhea duration could be used to stratify vaccine trial endpoints by severity based on its ability to predict death.